Generation of sodium halide endohedral metallofullerenes in the gas phase. (15th July 2020) - Fan, Xingting; Wang, Yiyun; Kong, Xianglei
Abstract : Rationale: Recent theoretical calculations show that ionic bond encapsulated endohedral metallofullerenes (EMFs) have great potential in the application of molecular electronic components. However, experimental study of these species is very limited, due to the difficulty in their generation. Thus, it is important to study the possibility and optimized conditions of these species generated in the gas phase. Methods: Mixtures of graphene and metal halides (MX), where M = Na, K; and X = Cl, Br, I, were used as the precursors for the experiments. Mass spectra were obtained in positive ion mode by laser irradiation of these mixtures of graphene and metal halides using a 7.0 T Fourier transform ion cyclotron resonance (FTICR) mass spectrometer equipped with a 355 nm YAG laser. Results: EMF ions of NaCl@C+ 2n (2n = 120–244), NaBr@C+ 2n (2n = 110–240), and NaI@C+ 2n (2n = 116–198) were observed in the laser ablation mass spectra. However, the encapsulated ion could not be replaced by Li or K in these experiments, indicating that the effects of the metal cation on the EMFs are larger than those of halide anions. Conclusions: Ionic bond encapsulated EMF ions of NaX@C+ 2n (X = Cl, Br and I, 110 ≤ 2n ≤ 244) were generated by laser ablation of the mixture of graphene and sodium halides, but no species containing lithium or potassium were observed. This work opens the possibilities of using laser ablation for the synthesis of large‐sized salt‐encaged EMFs. Further study of the mechanism for these processes is important for the generation of the missing species.